Errors due to sampling frequency of the electrocardiogram in spectral analysis of heart rate signals with low variability - Abboud, S.; Barnea, O. (1995 Computers in Cardiology, 1995)
Spectral analysis of the heart rate signal was studied in patients with low heart rate variability regarding an error that may occur when there is a specific relation between the averaged heart rate and the sampling frequency of the electrocardiogram. ECG waveforms were recorded from healthy subjects and from patients after heart transplant, digitized with different sampling rates and analyzed for spectral analysis of heart rate variability. It was found that in healthy subjects with high heart rate variability, accurate results can be obtained when the sampling rate of the ECG is greater than 125 Hz. In heart transplant patients, up to 100% error may occur when the sampling rate is below 1 kHz. It is concluded that for spectral analysis of the heart rate signal recorded from patients that are characterized with low heart rate variability, high sampling rate of the ECG signal is necessary (1 kHz).